Intersections of class and gender in learners’ conceptualisations of sexuality education at a private, all-girls school - Kylie Kuhl (South African Journal of Education, 2021)
In this article I explore the role that class, and its intersections with gender, play in shaping the way that learners at a private, all-girls school in South Africa conceptualise their sexuality education. Drawing on data from focus group discussions with 2 friendship groups of Grade 10 learners, the evidence reveals the multiple, intersecting and contradictory ways in which middle-class young women navigate class and gender. Firstly, learners, in drawing on a discourse of middle-class excellence, reproduced class difference in their discussion of attending a private school. Secondly, they drew on this class capital to position themselves as immune to many of the issues dealt with in sexuality education, particularly teenage pregnancy. Finally, a discussion of the gender exclusivity of their school revealed that this class capital was not always available to them, as they prioritised a discourse of heterosexual desirability over middle-class excellence in speaking about their interactions with boys. The findings reveal the complex and changing ways in which young middle-class women discursively reproduce, resist and navigate the intersecting classed and gendered systems of power that shape their particular schooling context.